Manual of Temporal Bone Exercises - Hildmann, Henning; Sudhoff, Holger; Dazert, Stefan; Hagen, Rudolf; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This lavishly illustrated manual includes extraordinary artwork and offers a unique overview of all important structures of, and surgical techniques for, the middle ear and the temporal bone, including: Outer aspects of the temporal bone Mastoid preparations Mastoidectomy Posterior tympanotomy Cochleostomy Facial nerve decompression Mastoid cavity Labyrinthectomy Middle ear preparations Exercises in tympanoplasty Approaches to the internal auditory canal Topographical studies of the temporal bone This manual provides the reader with the knowledge necessary to start operating on patients. It also supports experts to improve and teach their skills.
Drills -- Microscope -- Preparation and Planning -- Identify following structures prior to the surgical exercises -- Mastoid -- Antrostomy -- Mastoidectomy -- Identification of the semicircular canals -- Posterior tympanotomy -- Identification of the facial nerve in its mastoidal portion -- Cochleostomy -- Endolymphatic sac surgery -- Epitympanotomy -- Open mastoid cavity -- Facial nerve decompression -- Labyrinthectomy -- Translabyrinthine approach to the internal auditory canal -- Transtemporal approach to the internal auditory canal -- Perforation of the tympanic membrane -- Ossicular chain reconstruction -- PORP -- TORP -- Stapes surgery -- Malleovestibulopexy.
Keywords: Medicine; Neurosurgery; Otorhinolaryngology; Head -- Surgery; Surgery; Medicine & Public Health; Otorhinolaryngology; Oral and Maxillofacial Surgery; Head and Neck Surgery; Neurosurgery; Surgery